2015
DOI: 10.1089/brain.2013.0210
|View full text |Cite
|
Sign up to set email alerts
|

Functional Integration Between Brain Regions at Rest Occurs in Multiple-Frequency Bands

Abstract: Studies of resting-state fMRI have shown that blood oxygen level dependent (BOLD) signals giving rise to temporal correlation across voxels (or regions) are dominated by low-frequency fluctuations in the range of *0.01-0.1 Hz. These low-frequency fluctuations have been further divided into multiple distinct frequency bands (slow-5 and -4) based on earlier neurophysiological studies, though low sampling frequency of fMRI (*0.5 Hz) has substantially limited the exploration of other known frequency bands of neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
159
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(180 citation statements)
references
References 47 publications
(77 reference statements)
16
159
2
3
Order By: Relevance
“…The ALFF in the slow-5 band involving larger brain regions provides evidence for the above statement. The current result showed that greater ALFF values for the slow-5 band in infants localized more within primary sensory and motor cortices and to a lesser extent within default-mode regions, which was inconsistent with findings that greater ALFF values in the slow-5 band were mainly located in the default-mode network in adults (Gohel and Biswal 2015;Han et al 2011;Zuo et al 2010). The power distribution in the slow-5 band in infants, therefore, is distinct from adults.…”
Section: Differences In Alff Between Frequency Bandscontrasting
confidence: 99%
“…The ALFF in the slow-5 band involving larger brain regions provides evidence for the above statement. The current result showed that greater ALFF values for the slow-5 band in infants localized more within primary sensory and motor cortices and to a lesser extent within default-mode regions, which was inconsistent with findings that greater ALFF values in the slow-5 band were mainly located in the default-mode network in adults (Gohel and Biswal 2015;Han et al 2011;Zuo et al 2010). The power distribution in the slow-5 band in infants, therefore, is distinct from adults.…”
Section: Differences In Alff Between Frequency Bandscontrasting
confidence: 99%
“…The natural frequency or "spectral fingerprints" (Siegel, Donner, & Engel, 2012;Siegel & Donner, 2010) has been confirmed in high frequency range by electrophysiological studies Tobimatsu et al, 1999). Recent studies have shown the frequency-specific functional connectivity (Gohel & Biswal, 2015;Wu et al, 2008), amplitude (Zhang et al, 2015;Liu et al, 2013;Zuo et al, 2010), and regional homogeneity (Song, Zhang, & Liu, 2014), suggesting that frequency-dependent brain activities also exist in lowfrequency BOLD fluctuations. The multiple generative mechanisms of low-frequency neural oscillations also support regional-specific natural frequencies (Siegel et al, 2012;Rosanova et al, 2009;Sanchez-Vives & McCormick, 2000).…”
Section: Potential Mechanisms Of Ssbrsmentioning
confidence: 87%
“…However, recently, groups have begun to investigate the neuronal contribution of this frequency range. For example Gohel and Biswal (2015) recently demonstrated that resting-state networks (including the DMN) were consistently observed across multiple frequency bands, including slow-2 (0.198-0.50 Hz) and slow-3 (0.073-0.0198 Hz), which overlap with the SF1 frequency range (0.125-0.250 Hz) that we used. In their discussion, the authors suggest that this finding implies that there is a substantial neuronal contribution to this frequency range.…”
Section: Limitationsmentioning
confidence: 99%